Production of fish chips - the new approach - Bakar, Jamilah; Ruhani, Arlina; Sheikh Abdul Hamid, Nazimah; Che Man, Yaakob (2001)
Marine fish is the most important raw material for the processing of fishery products in Malaysia. This is generally true worldwide. However, with the increasing price of marine fish and gradual depletion of this natural resource, an alternative has to be sorted. Recent studies have shown that the aquaculture sector was the fastest growing food production sub-sector. Changing lifestyle and food habits are apparent in the Malaysian population. This is perhaps, in part, due to the rapid industrialization and a change in the family pattern. 'Keropok ikan' or fish chips as known in the Western vocabulary is a popular snack food and also as an accompaniment at main meals. They are presently processed from marine, underutilized and from off-season fISh spuies. Product is generally of low quality and high variability in physical characteristics such as thickness and physical appearance such as shape, although, undoubtly nutritious. This paper intend to propose the processing of fish chips from freshwater fish such as from tilapia species and also proposes a new method of processing whereby the raw ingredients are all in the dry form and the method is a modification of the traditional one. Since freshwater fwh is equally rich in its protein and other nutrient, therefore, no compromise is made on the nutritional aspect of the product.The current attitude of the public towards the characteristic of freshwater fish odour and flavour are dealt with by a pretreatment ofthe raw material. Thus due to the modified processing method, the product has a consistent physical appearance after frying and hence takes on a new identity.